Diagnostic Value of Shear Wave Elastography Combined with the Toronto Clinical Scoring System in Detecting Diabetic Peripheral Neuropathy (The Review of Diabetic Studies, 2025)
Background: Diabetic peripheral neuropathy (DPN) is a common microvascular complication of type 2 diabetes mellitus (T2DM) and a leading cause of foot morbidity. Nerve conduction studies (NCS) remain the reference standard but are time-consuming and assess predominantly large fibers. Shear wave elastography (SWE) enables non-invasive quantitative assessment of nerve stiffness. This study evaluated the diagnostic performance of tibial nerve SWE alone and in combination with the Toronto Clinical Scoring System (TCSS) in detecting DPN.Methods: In this prospective observational study, 60 patients with T2DM were enrolled over one year. Participants were categorized into DPN and non-DPN groups based on NCS findings. All subjects underwent TCSS evaluation, conventional ultrasonography for tibial nerve cross-sectional area (CSA), and SWE to obtain Emean, Emin, and Emax values bilaterally. Group comparisons, correlation analysis, and receiver operating characteristic (ROC) analysis were performed.Results: Tibial nerve stiffness parameters were significantly higher in the DPN group compared to the non-DPN group (p < 0.01). Mean right tibial nerve stiffness (Emean RT) demonstrated excellent diagnostic performance (AUC = 0.932; 95% CI: 0.872–0.993). SWE parameters showed strong positive correlation with TCSS scores (r ≈ 0.79, p < 0.01). Combining SWE with TCSS improved diagnostic sensitivity and specificity compared with either modality alone.Conclusion: Tibial nerve SWE is a reliable non-invasive imaging biomarker for DPN. When combined with TCSS, diagnostic accuracy improves significantly. SWE may serve as a practical adjunct screening tool in patients with T2DM.